Erythrocyte aggregation at non-steady flow conditions: a comparison of characteristics measured with electrorheology and image analysis - Kaliviotis, Efstathios; Ivanov, Ivan; Antonova, Nadia; Yianneskis, Michael (My University, 2010)
In the present study electro-rheology (Contraves LS30 viscometer-based system) and optical shearing microscopy (Lincam CSS450 system and image analysis) techniques have been utilized in order to provide quantitative data on the behaviour of the microstructural properties of whole normal human blood at non-steady flow conditions. The objective of this work is to contribute towards a better understanding of red blood cell aggregation at flow conditions similar to that occurring in a circulatory system and to aid the interpretation and validation of electro-rheological data through a quantitative comparison with data acquired with optical shearing microscopy. Electro-rheology is a promising technique that has been used to provide bulk fluid properties, showing potential for basic research and diagnostic purposes, whereas optical shearing techniques offer a direct assessment of blood microstructure at a cellular level. However, little information exists in the literature regarding the relationships between electro-rheological measurements and blood microstructural characteristics. The results showed that the different non-steady flow conditions affect differently the dynamics of aggregation varying from a parabolic-decrease to an inverted S-shape curve with time. For a wide range of the non-steady flows results obtained with the two different techniques agree to a difference between 1.2 and 12%.
Keywords: Aggregation index; Blood microstructure; Conductivity